Climate change and defoliation interact to affect root length across northern temperate grasslands. (15th September 2020) - Ma, Zilong; Chang, Scott X.; Bork, Edward W.; Steinaker, Diego F.; Wilson, Scott D.; White, Shannon R.; Cahill, James F.
Abstract: Grassland plants, especially their root systems, are dynamic and can buffer changes resulting from exposure to multiple stressors; however, the interactive stressor effects on root dynamics and associated above‐ground growth are poorly understood. Here, we examine the effects of changed precipitation and air temperature, and defoliation intensity on root length dynamics and above‐ground biomass using the third year data from a multifactor experiment conducted across three northern temperate grasslands. We found that root length was more sensitive to the changes in environmental and management conditions than root mass, demonstrating the importance of root length as an indicator of rapid root system changes. Across all sites, warming, altered precipitation and defoliation intensity interacted to affect root length while above‐ground biomass was only affected by defoliation intensity, indicating that the root system was more responsive than above‐ground biomass when climatic conditions change. Overall, drought reduced root length, particularly under low defoliation intensity, as well as in combination with warming and heavy defoliation, highlighting the risk of additive effects of such environmental stresses. Across unclipped plots, above‐ground biomass was positively associated with total root length, the latter of which further interacted with precipitation, to affect above‐ground biomass. Compared to defoliated communities, non‐defoliated plant communities exhibited a greater ability to maintain above‐ground biomass under drought conditions via increases in root system efficiency (the amount of above‐ground biomass produced per unit of root length invested). Our results highlight the rapid change of root length in the face of interactive stressors. We postulate that the degree of stability in above‐ground biomass is driven by the altered root system dynamics or species turnover. Future studies are warranted that more directly assess how root length responses under climate change impact other important plant traits in grasslands. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.